VEHICLES FOR REPAIR AND MAINTENANCE OF BRIDGE STRUCTURES - Kyslov, O. H.; Buhaievskyi, S. O.; Chuhuienko, S. O. (Science and Transport Progress, 2007)
The basic stages of bridge structure repairing and equipment necessary for the given works have been considered in this article.